SSP integrated with the local potential of toga village based on green economy toward scientific literacy and enterpreneurial interest: A systematic review - Khoirul Huda; Insih Wilujeng; Devy Alvionita; Musawwir Usman (JURNAL BIOEDUKATIKA, 2020)
Specific Subjects Pedagogy Biology based on green economy or more commonly known as (SSP) is a learning tool designed as a reference and framework for implementing learning by applying the principles of Green economy which can be applied to biology Students. The purpose of this systematic review research is to examine the theory of several previous studies in order to further find new theories about the integration of the learning concept of local potential of toga village with green economy concept in biology students toward Scientific Literacy and Entrepreneurial Interest. The method used is a systematic review which using 5 stages. The articles studied came from Google Scholar and ERIC data based, and then the search results were directed to national and international journals from 2010-2020. The results of the analysis showed that the concept of integration of the local potential of the toga village with green economy concept was a good and efficient, a SSP framework was formed that was integrated with the local potential of the toga village toward scientific literacy and entrepreneurial interest, as well as a great opportunity to use the concept of findings to some basic competencies in junior and senior high school.